(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The current research set out to examine the connection between the demographics on the attitudes and perspectives of rural adolescents in Maharashtra’s Latur district towards village development programs. This study’s researchers employed a random sample technique to choose the villages, talukas, and districts. The results showed that among rural adolescents, 68.65% had a positive attitude, 17.79% had a very positive attitude, and 13.56% had a negative attitude. Additionally, it was noted that a large portion of rural kids (86.44 percent) had a positive outlook on agricultural education and its potential dissemination via New York City youth groups. Apart from that, it was observed that 40.07 percent of the youth among rural areas see Nehru Yuva Kendra as the least effective medium for educating rural youth. The attitude of rural youth towards village development activities was shown to be positively and significantly correlated with age, education, religion, family type, family size, annual income, usage of information sources, extension contact, and accomplishment motivation according to the correlation coefficient (r).